Linux e-mail : set up, maintain, and secure a small office e-mail server - Haycox, Ian (From technologies to solutions., 2009)
"This book gives you just what you need to know to set up and maintain an email server. Unlike other approaches that deal with one component at a time, this book delivers a step-by-step approach across all the server components, leaving you with a complete working email server for your small business network. Based entirely on free, Open Source software, this book will show you how to set up and manage your email server easily"--Resource description page